Review on hazardous and noxious substances (HNS) involved in marine spill incidents—An online database - Cunha, Isabel; Moreira, Susana; Santos, Miguel M. (Journal of hazardous materials, 2015)
•Online database of hazardous and noxious substances involved in spill incidents.•Focus on the fate and weathering of HNS involved in previous spill incidents.•Information systematized for stakeholders involved in preparedness and response.•Analysis of 184 spilt HNS in 119 incidents in marine waters around the world.•Very little information on fate and weathering recovered due to poor documentation. In this review, we have collected information on the behavior, fate, weathering, and impact of hazardous and noxious substances (HNS) accidentally spilled at sea on the marine biota. The information was compiled on a datasheet and converted into a database that can be accessed by the general public (www.ciimar.up.pt/hns). Systematization of data is important to assist stakeholders involved in HNS spill preparedness and response, facilitating the incorporation of lessons from past incidents in the decision process. The database contains 184 entries of HNS spilled in 119 incidents in marine waters around the world. Data were analyzed in terms of HNS physical behavior in water according to SEBC (Standard European Behavior Classification) codes. The most common products involved in accidental spills in the marine environment were identified and major lessons highlighted. From the analysis, it was determined that most HNS spills were poorly documented and information was mistreated. In most cases, no monitoring programs were implemented following the incident. This conduct has occurred in 24 out of 119 incidents analyzed and has consequently limited the information on fate, behavior, and weathering of HNS spilled that could have been recovered. Major gaps were identified, and priorities and recommendations were drawn as a step toward improving preparedness and response to HNS spills.